Effect of various food types on the production and income of sea bass (Lates calcarifer Bloch) grown in brackishwater ponds - Hanafi, Hasan (Iloilo College of Fisheries, U. P. in the Visayas, 1991)
A study was conducted to determine the effects of various foods types on the production of sea bass (Lates calcalifer Bloch) grown in brackishwater ponds, and to determine the suitable food for sea bass. The study utilized twelve 250m2 experimental ponds at the Brackishwater Aquaculture Center, UPV College of Fisheries in Leganes, Iloilo. Fopur treatments with three replicates each were tested using the Randomized Complete Block Design. The treatments tested were : (1) Treatment I, shrimp feed with 43.6% crude protein. (2) Treatment II, trash fish, (3) Treatment III, Tilapia at 1:10 Sea bass-tilapia ratio, and (4) Treatment IV, moist formulated feed. Treatment II (trash fish) showed the highest production (445.33 kg/ha), followed by Treatment III (live food) (176.56 kg/ha), Treatment IV (moist formulated feed) (146.84 kg/ha), and Treatment I (shrimp feed) the lowest production (117.94 kg/ha). Additional tilapia at harvest in the treatments utilizing live fish food has 229.14 kg/ha. Analysis of variance showed highly significant differences (P> 0.01) among treatments. Growth response was expressed in terms of mean weight gain per day. The highest mean weight gain per day was obtained in Treatment II (0.97g), followed by Treatment III (0.65g) Treatment i (0.64g) and Treatment IV (0.40g). Analysis of variance showed no significant differences among treatments (P> 0.05). The best feed conversion ratio (dry weight basis) was opbtained in treatments II (2.21), followed by IV (4.28) and the poorest was in Treatment I (5.28). No significant differences (P> 0.05) were obtained among treatments Survival rate was highest in Treatment II (74.13%) followed by Treatment IV (56.27%), treatment III (43.20%) and the lowest in Treatment I (36%). Highly significant differences were observed among treatments (P. 0.01). Condition factor was significantly higher in Treatment ii (1.47) than the rest of the treatments Treatment I had condition factor of 1.38 which was significantly higher than treatment IV (1.29) and Treatment III (1.28). The difference between Treatments IV and III was not significant. Physico-chemical parameters such as water (temperature, salinity, dissolved oxygen, pH, depth and ammonia-N) were within tolerable levels for good growth of sea bass. Cost and return analysis showed that monoculture of sea bass fed by trash and polyculture of sea bass with tilapia are profitable.
Thesis (M. S. Fisheries) - U. P. in the Visayas, April 1991.
Keywords: Seabass; Food supply; Lates calcarifer Bloch; Feeds and feeding; Fisheries economics